BIG DATA DAN PENYEBARLUASAN PENGETAHUAN: PENGALAMAN PERPUSTAKAAN UNSYIAH - Taufiq A. Gani (Ikatan Pustakawan Indonesia, 2019)
Big data is a necessity for libraries. However, librarians still lack an understanding of the application pragmatically. The main obstacle is the level of mastery of librarians on information technology. Research and development must be directed at librarians' view of big data as an abstraction, the availability of tools to strengthen services and strategic operations, and easily re-implement existing systems and applications (reuse). This paper describes the system that is suitable for libraries to start the application of big data, the tools needed by libraries, how big data can do processing patterns, trends and associations related to library user behavior and interactions. This study produced a model of a big data system taken from the legacy application system that had been applied in the Unsyiah Library through reverse engineering. From verification of the model through the existing scenario, it can be seen that big data and cloud services can more easily acquire data on virtual user interaction through library web applications, the technical complexity of acquisition and managing data becomes abstracted. Furthermore, it is also seen that this system can dig deeper information about library performance. Trends and patterns for data can be identified more easily.